Empowering the voiceless. Disorders of consciousness, neuroimaging and supported decision-making - Timo Istace; Timo Istace (Frontiers in Psychiatry, 2022)
Patients suffering from (Prolonged) Disorder of Consciousness are deemed incompetent to give valid informed consent due to the presumed impairment of their cognitive functions and the impossibility to communicate with them. Neuroscientists have, however, discovered ways in which communication with some of these patients might be possible by using neuroimaging. This would for the first time make it possible to include them in the decision-making on their own medical treatment. In this article, I elaborate on the prospect of communicating with patients with impaired consciousness in order to obtain their informed consent. I first map the current state-of-the-art in neuroimaging research that exhibits the possibility of communicating with some of these patients. Secondly, I examine how obtaining informed consent from these patients might be possible, given that the specificities and limitations of communication via neuroimaging render the task of assessing their competence rather difficult. Thirdly, I identify some of the important ethical and legal considerations that have to be taken into account before introducing neuroimaging in clinical practice as a means to obtain informed consent. Lastly, I look into the concept of supported decision-making and how this concept relates to the use of neurotechnology to support minimally conscious patients in their abilities to decide over their own medical treatment.